Biodegradable Polymer-Based Microspheres for Depot Injection-Industry Perception - Kyatanwar, Anand; Nagarsenker, Mangal; Prabhakar, Bala (Recent Advances in Drug Delivery and Formulation, 2023)
The discovery of proteins and peptides marked the actual beginning for pharmaceutical companies to do research on novel delivery systems for delivering these therapeutic proteins. Biodegradable polymer-based microspheres for controlled-release depot injection are known for decades and have proved to be one of the best possible approaches. Despite being known for decades, the commercial success of microsphere-based delivery systems remains limited. Very few products are seen in the market with no generics available for approved brand products whose patents have either expired or are about to expire. All this points to the complexities involved in developing these delivery systems. Still, many hurdles remain in developing these drug delivery systems namely, poor drug entrapment, unwanted burst release, poor in vitro in vivo correlation, lack of proper in vitro testing methods, problems involved during scale-up, and the most important hurdle being sterilization of the product. To achieve successful product development, all of these technical difficulties need to be simultaneously dealt with and resolved. This article attempts to highlight the problem areas for these delivery systems along with the regulatory requirements involved and map the present status of these delivery systems.
Keywords: depot injection